2006
DOI: 10.1021/ie061077k
|View full text |Cite
|
Sign up to set email alerts
|

Method and Model for the Analysis of Gel-Blocking Effects during the Swelling of Polymeric Hydrogels

Abstract: This paper focuses on a method to determine the swelling pressure of polymeric hydrogels. The method is based on determining the swelling pressure at a defined volume of swelling that is smaller than the volume the gel can attain by free swelling to equlibrium. Data for one type of polymer particles made from weakly cross-linked and partly neutralized poly(acrylic acid) are presented for swelling in deionized water. For polymer volume fractions (φ P ) in the range of 0.05-0.30, swelling pressures in the range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…However, as the total acid group value of the nanosamples increased, the water retention values decreased and a gel-like material was obtained after sulfonation. Studies by Ulbrich and Parsons of polymeric hydrogels have reported that gel-like properties reduce water retention values (Wack and Ulbricht 2007;Waring and Parsons 2001).…”
Section: Resultsmentioning
confidence: 99%
“…However, as the total acid group value of the nanosamples increased, the water retention values decreased and a gel-like material was obtained after sulfonation. Studies by Ulbrich and Parsons of polymeric hydrogels have reported that gel-like properties reduce water retention values (Wack and Ulbricht 2007;Waring and Parsons 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Inside the material, the liquid might be transported by diffusion through the material matrix as well as along the interfaces between SAP and the matrix. In interaction with already existing swelling models23 these qualitative results can contribute to clarify the material transport processes taking place. This is the subject of current studies.…”
Section: Resultsmentioning
confidence: 66%
“…If, however, the porous part of the confinement is too low, the scale readout is also low (case 1 of Figure 2). This behavior can be explained with gel blocking [16,17,22] which describes the reduction of water inflow with increasing swelling of the gel layer in direct contact with water due to the confined geometry. Of all the investigated confinements, case 4 leads to the highest increase of the apparent mass (highest swelling pressure) due to the lowest µ 1sg (cf.…”
Section: Resultsmentioning
confidence: 99%
“…The latter method has the advantage that composition dependence of the swelling pressure is obtained in just a single experiment [9]. Progressing miniaturization of devices for pressure measurements stimulated during the last decade the development of small sensors utilizing the swelling pressure of gels [12][13][14][15][16][17]. In biology and medicine the swelling pressure plays a major role in the function of connective tissues and hence, methods have been developed to study for example the isometric compressive stress of cartilage in a sophisticated apparatus with feedback control to ensure strict volume constancy [18].…”
Section: Introductionmentioning
confidence: 99%